Level of Creative Thinking Effect Through Multiple Solution Task Type Problem-Solving on Learning Outcomes - Muhammad Kris Yuan Hidayatulloh; Supari Muslim; Erina Rahmadyanti; Euis Ismayati; Nita Kusumawati (JETL (Journal of Education, Teaching and Learning), 2020)
This study aims to: (1) analyze the level of creative thinking possessed by each class XI students of Building Drawing Technique (BDT); and (2) analyze the influence of the level of thinking on the learning outcomes of the cognitive, affective, and psychomotor domains. This type of research is correlational research through a quantitative approach method. The population in this study were all students in building expertise competencies at SMK Negeri 1 Nganjuk which included Geomatics and BDT. The sample used in this study was XI BDT class students. The instrument used in analyzing the level of creative thinking (LCT) is a problem-solving test sheet of the type of multiple solution tasks. The data analysis technique uses a linear regression test. The results of the study concluded that: (1) there were as many as 4 students included in the category of LCT 4 (very creative), there were 12 students included in the category of LCT 3 (creative), there are 11 students included in the category 2 LCT (quite creative), there are no students included in the category of LCT 1 (less creative), and there are as many as 11 students who included in the category of LCT 0 (not creative); (2) there is a significant influence between the level of creative thinking on the cognitive and psychomotor learning outcomes; and (3) there is a very significant influence between the level of creative thinking on the affective learning outcomes of class XI BDT students.